Gereja dalam Arus Politik Transaksional: Mewaspadai Politik Transaksional dalam Moment Pemilu - Ove Oktavian Purba (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2023)
AbstractPolitical Power, where in a democratic process such as the direct Election of Regional Heads to elect regents, mayors, governors, or members of the legislature today cannot be separated from the existence of the power of political capital from the candidates. This paper will discuss the Transactional Politics that occurs at the moment of the Election. It is hoped that this article will serve as a warning and a discourse that can be shared among the congregation considering that it is possible for important figures in the church to get trapped or involve themselves in the currents of transactional politics where they serve. An important point that will also be discussed is that the Church as a Religious Institution can be a source of Ethics and Morals for its followers in carrying out political activities as a form of service in the midst of society and the world. Abstrak Kekuatan Politik, di mana dalam proses demokrasi seperti Pemilukada langsung untuk memilih bupati, walikota, gubernur atau anggota legislatif dewasa ini tidak lepas dari keberadaan kekuatan pemodal politik dari kandidat calon. Tulisan ini akan membahas mengenai Politik Transaksional yang terjadi pada momen Pemilu. Tulisan ini diharapkan menjadi peringatan dan sebuah wacana yang dapat di sharing kan di tengah-tengah jemaat mengingat mungkin saja tokoh-tokoh penting dalam gereja terjebak ataupun melibatkan dirinya dalam arus politik transaksional di mana dia melayani. Pokok penting yang juga akan dibahas adalah Gereja sebagai sebuah Institusi Keagamaan dapat menjadi sumber Etika dan Moral bagi pengikutnya dalam melakukan aktivitas Politik sebagai bentuk pelayanannya di tengah-tengah masyarakat dan dunia.